2016
DOI: 10.1007/978-3-319-33111-9_15
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Potential of Delivering Employer Information Requirements in BIM Enabled Construction Projects in Qatar

Abstract: Part 4: Building Information Modeling (BIM)International audienceEmployer’s Information Requirements (EIR) is a key document for the successful delivery of construction projects using Building Information Modeling (BIM). EIR sets out the information to be delivered and the standards and processes to be adopted by the suppliers as part of their project delivery approach. The concept of EIR has been developed by the UK BIM Task Group as a holistic framework for the UK construction industry to deliver the UK cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…This phase of the research is based on previous literature review, policy documents, and research interviews with major QCI stakeholders, conducted and analysed by Hafeez et al (2016) Secondly, the selection of the key performance indicators (KPIs) for sustainable building operation and facility management is done through the study of existing literature and standards. The different values found in EN 15221-7:2012 standard, sustainable facility management approach and other approaches as Jansson et al (2013), Chen et al (2015), Zhang and El-Gohary (2016) and the different relevant sustainability assessment schemes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This phase of the research is based on previous literature review, policy documents, and research interviews with major QCI stakeholders, conducted and analysed by Hafeez et al (2016) Secondly, the selection of the key performance indicators (KPIs) for sustainable building operation and facility management is done through the study of existing literature and standards. The different values found in EN 15221-7:2012 standard, sustainable facility management approach and other approaches as Jansson et al (2013), Chen et al (2015), Zhang and El-Gohary (2016) and the different relevant sustainability assessment schemes.…”
Section: Methodsmentioning
confidence: 99%
“…A recent survey within main stakeholders in QCI showed the level of pervasion and maturity of BIM use and adoption (Hafeez et al, 2016). According to the survey, a list of BIM related requirements, which can be included in the aforementioned EIR areas, were commonly found in a big share of contracts (68%).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the findings represent a market that is optimistic and aware, but inexperienced in BIM (BuildingSMART, 2011). Also, very limited amount of research has been carried out so far such as Dawood and Vukovic (2015), Ahmed et al (2014), Vukovic et al (2015), Hafeez et al (2015), Skaik and Ali (2013), Omar (2015). In addition to that, is the absence of any governmental mandate to encourage BIM adoption.…”
Section: Bim Implementation and Maturity In The Aec Industrymentioning
confidence: 99%
“…A recent study conducted by Hafeez et al (2016) which investigates a framework for delivering EIR in the Qatar construction Industry; "QEIR". The study resulted in many useful recommendations and tips for delivering quality EIRs, shown in Figure 7 below.…”
Section: Framework For Defining Construction Clients' Requirementsmentioning
confidence: 99%